Stenotrophomonas rhizophila a Novel Plant-Associated Bacterium With Distinguished PGPRs Properties - Asmaa Elhosieny; Mona Zayed; Shawky Selim; Ayman Yassen; Norhan Abdel Aziz (Arab Universities Journal of Agricultural Sciences, 2023)
Stenotrophomonas sp. is a plant-associated rhizospheric bacteria. It can enhance plant productivity. It acts as a mineral dissolution and growth promoter for plants under salt-stress conditions. The selected isolates revealed the general morphological and biochemical characteristics of Stenotrophomonas sp. All the isolates exhibited the highest growth density after 15 hr. at 30oC, resistance to different levels of salinity, different pH levels, and different temperature degrees. Also, the isolates revealed their capabilities to solubilize phosphorus and potassium and to produce different phytohormones. The isolate X.M9 exhibited the highest growth performance in the form of 1.376,1.326,1.292,1.053 and 1.059 OD in most salts’ concentrations compared to all tested isolates respectively. In addition, it (X.M9) exhibited the highest resistance to low temperatures 10 and 15oC being 0.917 and 1.354 OD respectively. The isolate X.M9 recorded the highest IAA of 83.73 mg/100ml compared to all the tested isolates. The isolate X.M9 was identified using 16 SRNA sequencing and submitted to the GenBank database un-der accession number No: OP050187 as Stenotrophomonas rhizophila.